THEORETICAL FUNDAMENTALS OF MEDICAL INSTITUTION COMPETITIVENESS POTENTIAL DEVELOPMENT MANAGEMENT - BAKSALOVA, OLGA; SHELEST, IEVGENIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Theoretical and methodological principles of medical institution competitiveness potential development management are explored in the article. The concept of medical institution competitiveness is considered as a complex, step-by-step, multifaceted, dynamic process involving the formation and implementation of management decisions and measures to sustainably increase competitiveness and dynamically increase competitive advantages and competencies of the medical institution on an innovative basis. It was found that the following components of the theoretical basis of medical institution competitiveness potential development management are the most widely used and studied among domestic scientists and practitioners: factors of competitiveness; the nature of the factors of influence; vectors, directions of competitiveness development and quality of medical services; principles, functions and patterns of development of competitiveness of medical institutions and services, etc. Therefore, it was determined that the delineation of these components is extremely important to consider in the process of developing a system of measures to increase the competitiveness of any medical institution, which will contribute to their efficiency and relevance. In the current Ukrainian and foreign publications, the problems of quantitative assessment of the level of medical institution competitiveness are covered quite widely. In these works, researchers argue the use of different approaches to calculate competitiveness indicators; advantages and disadvantages of certain methodological approaches; the need to take into account various factors in assessing the level of medical institution competitiveness etc. Various ways of applying the method of expert assessments in determining the level of competitiveness of organizations are proposed. The use of this method can often reduce the reliability and objectivity of research results. In general, the assessment of the level of competitiveness is currently carried out taking into account the influence of market factors, which usually give an incomplete description of the organization under study. Therefore, in order to obtain reliable results of competitiveness assessment, it is necessary to apply a system of complex factors that take into account the specifics of not only domestic medical organizations, but also medical services.